Immunoglobulin A and M levels in premature infants with gastroenteritis. Issue 249 (October 1971) - Panayotou, P.; Papadatos, C.; Papaevangelou, G.; Alexiou, D.; Skardoutsou, A.; Kourea, E.
Abstract : Eleven premature babies with an infection of the gastrointestinal tract were followed from birth up to the first month of life in an attempt to correlate the effect of acute localized infections of the gut to IgA and IgM immunoglobulin synthesis. The results were compared to those of 17 prematures comparable in birthweight and gestational age with no clinical or bacteriological evidence of an intestinal infection. There was a significant increase of serum IgA and a slight but not significant increase of IgM level in infected babies as compared to the healthy group of prematures. It is suggested that micro-organisms causing localized infections of the gastrointestinal tract stimulate immunoglobulin A producing sites of the intestinal wall. This results in rapid production of secretory antibody. In the course of this localized infection, replication of bacteria in the lymphoid tissue of the intestinal wall stimulate immunologically competent cells in direct proximity to the alimentary tract, causing increased serum IgA levels.